Rekonstruksi Pendidikan Islam Bervisi Inklusif-Multikultural sebagai Paradigma Transformasi Epistemologis Pendidikan Nasional - Muqoyyidin, Andik Wahyun; Widiyaningsih, Puspa Mia (Jurnal Pendidikan Islam, 2021)
This discourse departs from the sharp criticism of some groups towards the learning of religious education, which tends to be exclusive at various levels of education which is allegedly limited to promoting their correct religious mindset, and other groups are seen as misguided. The purpose of this discourse is to explore the design and format of the reconstruction of Islamic education with an inclusive-multicultural vision as a paradigm for the epistemological transformation of national education. This library research-based discourse resulted in findings of the importance of reconstructing the components of Islamic education with an inclusive-multicultural vision, especially in curriculum design, educator figures, and the effectiveness of learning strategies. The redesign of these components is expected to be a paradigmatic basis for the ideal transformation of the national education model in the future.